DNA barcoding: the social frontier. Issue 8 (1st October 2007) - Larson, Brendon MH
Abstract : DNA barcoding has been promoted as the holy grail of biodiversity conservation. Its proponents envision a time when anyone will be able to use a portable Life Barcoder to identify a fragment of an organism to the species level within seconds. While several critics have questioned whether DNA barcoding will work technically, claims about its social benefits have not been scrutinized. Here, I focus on two prevalent assumptions about the Life Barcoder: that it will democratize access to biodiversity and that it will increase appreciation for it. I argue that neither of these assumptions is well supported, since a Life Barcoder will prioritize one way of knowing over others, and create a technological distance between people and organisms. Consequently, DNA barcoding may not benefit conservation as much as its proponents assume.